2021
DOI: 10.1039/d1cp01628h
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast energy transfer between lipid-linked chromophores and plant light-harvesting complex II

Abstract: We characterize the photophysical interactions between lipid-linked chromophores and plant light-harvesting proteins incorporated into nanodiscs using optical spectroscopy, simulations and theoretical modelling.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 91 publications
(137 reference statements)
0
13
0
Order By: Relevance
“…Overall, these results show that the degree of quenching achieved with in-membrane electrophoresis can be controlled by simple modifications to the starting composition of the membrane. This could allow this platform to be used to investigate quenching over a wide dynamic range of concentrations for many other electrostatically charged fluorophores, such as different organic molecules or even membrane proteins, such as the light-harvesting pigment-protein complexes involved in photosynthesis in plants and bacteria. ,,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, these results show that the degree of quenching achieved with in-membrane electrophoresis can be controlled by simple modifications to the starting composition of the membrane. This could allow this platform to be used to investigate quenching over a wide dynamic range of concentrations for many other electrostatically charged fluorophores, such as different organic molecules or even membrane proteins, such as the light-harvesting pigment-protein complexes involved in photosynthesis in plants and bacteria. ,,, …”
Section: Resultsmentioning
confidence: 99%
“…This could allow this platform to be used to investigate quenching over a wide dynamic range of concentrations for many other electrostatically charged fluorophores, such as different organic molecules or even membrane proteins, such as the light-harvesting pigmentprotein complexes involved in photosynthesis in plants and bacteria. 38,39,45,46 The limitations of the electrophoresis technique and the analysis methodology should be briefly discussed in a wider context. First, the electrophoresis technique has the requirement that the fluorescent probe must respond to an electric field; therefore, alternative lipid-linked molecules that have either (single or multiple) negative or positive charges are likely to be effective, but neutral molecules will not undergo electrophoresis.…”
Section: Consistency Of Concentration Profiles Across Multiple Membra...mentioning
confidence: 99%
“…Our previous work has shown that plant LHCII [40, 41] can be “enhanced” with lipid-linked Texas Red (TR) chromophores when they are co-assembled into model membranes in the form of either lipid vesicles [36] or lipid nanodiscs [42]. This TR moiety is amphiphilic and is tethered to lipid headgroups which allow the possibility of close contact with membrane proteins ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In these studies we demonstrated several advantages of using lipid-tagged chromophores: (i) the system is modular in the sense that dyes can be incorporated at a wide range of concentrations, (ii) LH proteins can be “enhanced” whilst in a biologically-relevant membrane environment, and (iii) membranes readily adsorb to surfaces making them amenable to surface-based nanotechnologies [36]. Evidence was presented for attractive interactions occurring between the TR chromophores and LHCII proteins which increased the rate of energy transfer [42]. For the current study, we hypothesized that it should be possible to enhance other LH complexes in a similar manner, and chose to study the LH2 antenna from Rhodobacter ( Rba. )…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation